Customer loyalty through social networks: Lessons from Zara on Facebook - Gamboa, Ana Margarida (2022)
Companies’ escalating investment in social media–—in particular, in Facebook–—has become reality. However, most firms still do not see social networks as a vehicle for cultivating and winning customer loyalty, but rather as a resource for creating brand awareness. In this article, we offer a different view. By examining fans and non-fans of the Zara brand on Facebook, we discovered that Facebook enhances the relations that increase loyalty via trust, customer satisfaction, perceived value, and commitment. Our results revealed that these relations are stronger for fans of the brand than for non-fans, and suggest that customer satisfaction is the strongest determinant of loyalty. This indicates a new opportunity for marketing managers to achieve customer loyalty: Facebook.